ON THE EXPERIMENTAL BICULTURE OF THE SEA BASS, LATES CALCARIFER (BLOCH) WITH OREOCHROMIS MOSSAMBICUS (PETERS) - Purushan, K S (Indian Journal of Fisheries, 2011)
has identified Sea bass (Lates calcarifer) culture as one of priority areas to develop aquaculturc industry (Kungvankij, 1986). In the south cast Asian countries, commercial culture of L. calcarifer has received great attention following the success achieved in its artificial seed production (Brohmanoda, 1982; Maneewong, 1986; Awang, 1986)